Icelandic wedding (North Dakota State University Libraries, Institute for Regional Studies;)
Group photograph showing a wedding couple surrounded by a large group of people, some dressed in traditional Icelandic costumes. Gelatin silver prints; 13 x 20 cm. "An Icelandic Wedding" - handwritten on back of photograph. Title supplied by staff. Photographer unknown.